Chock, angela, soprano, Malaysia - Ang, Lay Hoon (ISEAS Publishing Institute of Southeast Asian Studies, 2012)
A who's who list of prominent south-east asians of chinese descent has been compiled for the first time, in a book that gives an insight into the lives and achievements of the men and women who have helped to shape the region. Titled south-east asian personalities of chinese descent, A biographical dictionary, the 1,400-page tome features 608 people from 10 countries, all well-known names from the past and present centuries. They include influential personalities from various professions and fields, from statesmen, businessmen and religious leaders to pop stars, artists and athletes. Singapore has the most entries - 162 - including prime ministers Lee Kuan Yew, Goh Chok Tong and Lee Hsien Loong; entertainers Dick Lee and Fann Wong; eye surgeon Arthur Lim; entrepreneur Sim Wong Woo; and olympians Tan Howe Liang and Jing Junhong. Next is Indonesia, with names such as businessmen Soedono Salim - better known as Liem Sioe Liong - and banker Mochtar Riady; followed by Malaysia, with notables such as Malayan Communist Party leader Chin Peng, opposition politician Lim Kit Siang and badminton champ Lee Chong Wei.